Analysis of Rice Price Volatility in Medan City, Indonesia - Wibowo, Rulianda Purnomo; Pebriyani, Dian; Indriyanti, Tietin (Agro Bali : Agricultural Journal, 2025)
One of the primary challenges faced by government policies concerning agricultural commodities is maintaining food price stability. Instability in food prices can have significant economic, political, and social repercussions. This study provides an in-depth analysis of rice price fluctuations on a daily basis, offering a clearer understanding of rice price volatility in Medan. Through seasonality and volatility analysis, this research examines the changing trends in rice prices and their associated fluctuations. It is revealed that rice prices in Medan peak in February, and  the lowest rice prices occur in December. The rice prices were more volatile before the pandemic than after it. During the pre-pandemic period, the correlation between the prices of various food items was relatively low, meaning that the prices of different commodities were not strongly linked. However, in the post-pandemic period, the correlation between rice prices and other food items in Medan became more significant, suggesting that the prices of rice were more closely tied to those of other essential foodstuffs. Although rice price volatility in Medan is generally low throughout most of the year, the government should focus particular attention on the months between October and February, when volatility tends to be higher due to factors such as seasonal demand spikes and external influences like weather conditions. By proactively managing supply and demand, ensuring adequate rice stocks, and supporting local rice production, the Medan government can more effectively navigate periods of heightened volatility and ensure that rice prices remain stable and affordable for all consumers